2022
DOI: 10.1186/s12864-022-08708-0
|View full text |Cite
|
Sign up to set email alerts
|

In silico characterization, molecular phylogeny, and expression profiling of genes encoding legume lectin-like proteins under various abiotic stresses in Arabidopsis thaliana

Abstract: Background Lectin receptor-like kinases (Lec-RLKs), a subfamily of RLKs, have been demonstrated to play an important role in signal transduction from cell wall to the plasma membrane during biotic stresses. Lec-RLKs include legume lectin-like proteins (LLPs), an important group of apoplastic proteins that are expressed in regenerating cell walls and play a role in immune-related responses. However, it is unclear whether LLPs have a function in abiotic stress mitigation and related signaling pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 99 publications
(101 reference statements)
0
3
0
Order By: Relevance
“…In a previous study conducted on 220 microarray samples of A. thaliana available in the GEO, it was also shown that under drought conditions, the AT5G03350 gene, encoding salicylic acid-induced legume lectin-like protein 1, was suppressed 7.9 times (Shaik et al, 2013). It seems to be involved in A. thaliana responses to multiple environmental stresses (including cold, high light, oxidative, ozone, and wound) and SA-mediated processes occurring in the effector-induced immune response (Armijo et al, 2013;Biswas et al, 2022). Due to the unusual structure of the legume lectin domain, proteins of this family may have a wide range of carbohydrate-binding specificity (Sharma et al, 1997), which possibly determines their diverse functions (including involvement in symbiosis, defense mechanisms against bacterial infection, enhanced tolerance against insects, salinity, and stomatal closure) (Van Holle et al, 2017).…”
Section: Proteins With Interaction Domains (With Proteins or Polysacc...mentioning
confidence: 99%
“…In a previous study conducted on 220 microarray samples of A. thaliana available in the GEO, it was also shown that under drought conditions, the AT5G03350 gene, encoding salicylic acid-induced legume lectin-like protein 1, was suppressed 7.9 times (Shaik et al, 2013). It seems to be involved in A. thaliana responses to multiple environmental stresses (including cold, high light, oxidative, ozone, and wound) and SA-mediated processes occurring in the effector-induced immune response (Armijo et al, 2013;Biswas et al, 2022). Due to the unusual structure of the legume lectin domain, proteins of this family may have a wide range of carbohydrate-binding specificity (Sharma et al, 1997), which possibly determines their diverse functions (including involvement in symbiosis, defense mechanisms against bacterial infection, enhanced tolerance against insects, salinity, and stomatal closure) (Van Holle et al, 2017).…”
Section: Proteins With Interaction Domains (With Proteins or Polysacc...mentioning
confidence: 99%
“…Furthermore, researchers have also mapped the position of corresponding protein genes involved in RSS biosynthesis and observed that the majority of them were present on chromosomes 1, 2, 3, and 5 ( Figure 1 A,B) along with the protein/genes of ROS and RNS biosynthesis in Arabidopsis [ 28 ]. In addition, conserved motif analysis and gene sequence alignments demonstrated that all the reactive species producing enzymes/proteins have a highly conserved arrangement of motifs with varying sequences ( Figure 1 C and Figure 2 A) [ 29 ]. The phylogenetic and gene co-expression analysis ( Figure 2 B,C) of the major reactive species producing enzymes/proteins diverge from one another as they evolve from a common ancestor, and co-expression of the corresponding genes is essential for activating the transcription of stress-responsive genes and transcription factors [ 28 , 29 ].…”
Section: Rss Signaling In Plantsmentioning
confidence: 99%
“…In addition, conserved motif analysis and gene sequence alignments demonstrated that all the reactive species producing enzymes/proteins have a highly conserved arrangement of motifs with varying sequences ( Figure 1 C and Figure 2 A) [ 29 ]. The phylogenetic and gene co-expression analysis ( Figure 2 B,C) of the major reactive species producing enzymes/proteins diverge from one another as they evolve from a common ancestor, and co-expression of the corresponding genes is essential for activating the transcription of stress-responsive genes and transcription factors [ 28 , 29 ].…”
Section: Rss Signaling In Plantsmentioning
confidence: 99%